MAGNETITE SURFACE CHARGE STUDIES TO 290°C FROM IN SITU PH TITRATIONS - Wesolowski D.J.; Machesky M.L.; Palmer D.A.; Anovitz L.M. (My University, 2000)
The proton-induced surface charge of magnetite was investigated in 0.03 and 0.30 molal sodium trifluoromethanesulfonate solutions from 25°C to 290°C by potentiometric titrations using a stirred hydrogen electrode concentration cell. Pure magnetite with excellent crystallinity was produced by reaction with the Ni/NiO/H2O hydrogen fugacity buffer at 500°C. Inflection points in the 0.03 molal proton sorption isotherms (pHinfl) at 6.50, 6.24, 5.65, 5.47, 5.31 and 5.55 at temperatures of 50°C, 100°C, 150°C, 200°C, 250°C and 290°C, respectively, were used as estimates of the pristine point of zero charge (pHppzc) for modeling purposes. These pHinfl values parallel 1/2 pKw and agree within the assigned uncertainty (+/-0.3 pH units) at all temperatures with independent estimates of the pHppzc calculated from an extension of 88the revised MUSIC model. The surface charging can be adequately described by a one-pK model with a surface protonation constant fitted to the pHinfl values, and giving the standard state thermodynamic properties log KH,298=7.00, ΔH298°=-32.4+/-0.8 kJ/mol and constant ΔCp=128+/-16 J K-1 mol-1, with ΔS298° assumed to be equal to that of rutile protonation (25.5+/-3.4 J K-1 mol-1. The 0.03 and 0.30 molal proton sorption isotherms also exhibit pHs of common intersection (pHcip) at 6.33, 5.78, 5.37, 4.82, 4.62 and 4.90 at 50°C, 100°C, 150°C, 200°C, 250°C and 290°C, respectively. The difference between the pHcip and pHppzc#pHinfl values can be related to specific binding of Na+ on the negatively charged surface, which increases with increasing temperature, although the pHcip values may also be affected by dissolution of the solid. The electrical double layer model includes a basic Stern layer capacitance, with specific cation and anion binding at the Stern layer, and a fixed diffuse layer capacitance computed from Guoy-Chapman theory. To fit the steepness and asymmetry of the charging curves above the pHppzc, an additional cation binding constant was invoked, which allows the cation to experience the surface potential. Significant kinetically controlled dissolution of magnetite was observed below the pHppzc, which may be a result of leaching of Fe2+ from the surface, to produce a magnetite+hematite assemblage, despite the high hydrogen partial pressures (ca. 10 bars) used in these experiments.
Keywords: MAGNETITE; POINT OF ZERO CHARGE; SURFACE PROTONATION; POTENTIOMETRIC TITRATION